The six attributes of a leadership mindset flexibility of mind, mindfulness, resilience, genuine curiosity, creating leaders, enterprise thinking - Joe Britto (Carmarthen, Wales ; Williston, VT Crown House Publishing, 2019)
We can find a different way of leading by developing a different way of thinking. And the first step in growing a leadership mind-set is taking responsibility for making that shift happen.
Keywords: Leadership--Psychological aspects